2013
DOI: 10.1080/02701960.2013.830114
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Later Life: Examining Beliefs and Perceptions of Undergraduate Students

Abstract: Understanding students' beliefs and perceptions of sex/sexuality in later life can reduce and prevent ageist myths and stereotypes. The objective of this study was to gauge undergraduate students' knowledge of several myths, stereotypes, and facts regarding sex/sexuality in later life, including lesbian, gay, bisexual, and transgendered (LGBT) older adults. More than 85% of students held a positive view of sex/sexuality in later life with 65% believing that they would engage in sexual activity past age 80 (N=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Studies have indicated that younger adults have accepting, tolerant, open-minded and positive attitudes towards sexuality in later life (Allen and Roberto 2009;Freeman et al 2014). A survey of college students regarding their sexual attitudes and behaviors, both currently and projecting into later life, found that although younger adults were optimistic about continued sexual enjoyment in later life, they also believed many of the current myths about ageing.…”
Section: Attitudes and Perceptions Of The Young Towards Older People'mentioning
confidence: 99%
“…Studies have indicated that younger adults have accepting, tolerant, open-minded and positive attitudes towards sexuality in later life (Allen and Roberto 2009;Freeman et al 2014). A survey of college students regarding their sexual attitudes and behaviors, both currently and projecting into later life, found that although younger adults were optimistic about continued sexual enjoyment in later life, they also believed many of the current myths about ageing.…”
Section: Attitudes and Perceptions Of The Young Towards Older People'mentioning
confidence: 99%
“…Educational intervention is a beneficial supplement for lack of knowledge and negative attitudes towards sexuality in older people (Ewen & Brown, 2012;Freeman, Sousa, & Neufeld, 2014). Several meaningful patterns found in current studies reviewed clearly demonstrated the necessity of developing practical care guidelines and training for healthcare professionals (Bauer et al, 2013;Hardacker et al, 2014;Jones & Moyle, 2016;Shuttleworth et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…Ageist beliefs and negative attitudes affect quality of care, and negatively impact social behaviours and institutional treatment towards older adults, such as differential treatment from physicians (Bouman & Arcelus, 2001; Gewirtz-Meydan & Ayalon, 2016). Studies conducted in the past decade indicate that professional care providers are more accepting, tolerant, and open-minded towards sexuality in later life (Bouman, Arcelus, & Benbow, 2006; Freeman, Sousa, & Neufeld, 2014) than in the past. However, they often consider older adults’ sexuality as outside their scope of practice and lack the knowledge and confidence to treat or refer to issues related to sexuality (Haesler, Bauer, & Fetherstonhaugh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that the aged are not expected to have sexual relationships, and sexuality in later life is considered non-existent (Sharpe, 2004), unimportant, inappropriate, or irrelevant (Cooley, 2002; Henry & McNab, 2003). Although many people still hold beliefs about what is “normal” or “appropriate” sexual behaviour, studies conducted in the past decade indicate more liberal and tolerant attitudes regarding older adults’ sexuality (Bouman et al, 2006; Freeman et al, 2014). However, most of the discussion about older adults’ sexuality assumes heterosexuality and lacks awareness of lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI) issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation